(Ctm)PrP and ER stress: A neurotoxic mechanism of some special PrP mutants - Shi, Qi (Landes Bioscience, 2011)
The pathogenic agent is hypothesized to be PrP(Sc) in prion diseases. However, little accumulation of PrP(Sc) is repeatedly observed in some kinds of natural and experimental prion diseases, including some special genetic human prion diseases. One of the specific topology forms of PrP, (Ctm)PrP, representing a key neurotoxic intermediate in prion disorders, has been testified in cell-free translation systems and transgenic mice models. Recently, some studies have showed that point-mutations within the hydrophobic transmembrane region increase the amount of (Ctm)PrP in cells, such as human homologue A117V which is associated with GSS and G114V associated with gCJD, while the mutations outsides transmembrane region do not. The retention of the (Ctm)PrP in ER subsequently is able to induce ER stress and apoptosis, which is supported by upregulation of ER chaperone synthesis, such as Grp78, Grp58, Grp94, Bip and the transcription factor CHOP/GADD153. In conclusion, some kinds of intermediate forms of PrP(Sc), including (Ctm)PrP, may work as the ultimate cause of neurodegeneration.